Review on molecular communication - Zuo-peng LI; Jing ZHANG; Shao-bin CAI; Yong WANG; Jun NI (Tongxin xuebao)
Bio-inspired molecular communication (MC) is a kind of communication technology using biochemical mole-cules as the information carrier and applied to interconnect nano-machines to constitute the distributed nano-networks.The definition and properties of MC,applications of nano-networks based on MC,important research activities and pro-jects of MC were generalized.With particularly concerning the propagating mechanism of information molecules,the architecture of MC system was introduced.From the aspects of the design and implementation of system,theory research and nano-networks based on MC,the status of current research and development of MC was summarized and analyzed,in addition,future research trends was prospected.